Pengaruh pemahaman konsep dan minat baca terhadap kemampuan literasi matematika - Naziliati Naziliati; Anwar Mutaqin; Ihsanudin Ihsanudin (Universitas Sultan Ageng Tirtayasa, 2022)
The background of the problem is based on the low mathematics litercy of Indonesian students in PISA. Meanwhile, mathematics literacy is on of the abilities that must be mastered by students to implement mathematic in everyday life. The implementation of this research took place at MAN 1 Serang City of 2021/2022 academic year. The purpose of the study was to determine the effect of mathematics concepts understanding and reading interest on mathematics literacy skills simultaneously. The research method used is quantitative method with correlational research type. The sample involved in this study consisted of 31 students with the population is all grade XI students of MAN 1 Serang City as many as 290 students. The instruments used are test and non-test instruments. The results of this research is there is a positive and significant effect simultaneously between understanding of mathematics concepts and reading interest on mathematics literacy skills. The multiple correlation coefficient obtained is 0.658 which means that the effect of mathematics concepts understanding and reading interest simultaneously on mathematical literacy skills is 43%. The remaining 53% is influenced by other factors not examined.